The Influence of Islamic Spiritual Values on Students' Mental Health: A Special Focus on Tawakkul (توكُّل), Sabr (صبر) and Shukr(شكر) - Muhammadu Ibrahim Nasrin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Islamic spiritual values, derived from the Qur'an and Sunnah, are central to the daily lives of Muslims and play a crucial role in shaping their attitudes, behaviours, and social interactions. These values offer a holistic framework for personal growth and communal well-being. Among them, Tawakkul (توكُّل) (trust in Allah), Sabr (صبر) (patience), and Shukr(شكر) (gratitude) are core principles that guide the spiritual and moral conduct of individuals. Tawakkul(توكُّل) emphasises a balance between personal effort and reliance on divine will; Sabr(صبر) encourages perseverance during adversity; and Shukr(شكر) promotes gratitude for divine blessings. This study adopts a qualitative research approach to explore the theoretical foundations and practical implementation of Islamic teachings in diverse educational settings, focusing on how these spiritual values contribute to students’ mental health. The findings highlight that the integration of Tawakkul (توكُّل), Sabr (صبر), and Shukr(شكر) within religious education fosters emotional resilience, spiritual strength, and inner peace. Islamic teachings support the notion that these values can alleviate stress, reduce anxiety, and enhance psychological well-being. In educational environments, Sabr (صبر) serves as a vital coping mechanism, Tawakkul (توكُّل) provides spiritual reassurance, and Shukr(شكر) cultivates positive emotional states. Furthermore, students actively engaged in religious activities report lower stress levels and stronger social support systems. The study concludes that Islamic education, when effectively integrated, not only nurtures spiritual development but also offers valuable contributions to mental health support among students.